2021
DOI: 10.1136/bcr-2020-238177
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-related disease of the thyroid gland

Abstract: IgG4-thyroid-related disease (TRD) represents an uncommon spectrum of diseases, with four subcategories established so far, IgG4-related Hashimoto’s thyroiditis, fibrosing variant of Hashimoto’s thyroiditis, Riedel’s thyroiditis and Graves disease with elevated IgG4 levels. We report the case of a 59-year-old woman presenting with painless cervical swelling and hypothyroidism. Thyroid gland was enlarged and distinctively very hard, with reduced mobility. Neck ultrasonography showed multiple nodularity and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As mentioned, a small number of patients confirmed with Hashimoto’s thyroiditis develop its fibrotic variant, with this entity belonging to IgG4-RTD [ 88 ]. Most authors consider that the list of IgG4-RTD includes four distinct types of conditions, with Hashimoto’s thyroiditis being distinct from its fibrotic variant [ 88 , 89 ]. Some suggested that identifying a high level of serum IgG4 in one patient with Hashimoto’s thyroiditis represents an early predictor for developing its fibrotic variant [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, a small number of patients confirmed with Hashimoto’s thyroiditis develop its fibrotic variant, with this entity belonging to IgG4-RTD [ 88 ]. Most authors consider that the list of IgG4-RTD includes four distinct types of conditions, with Hashimoto’s thyroiditis being distinct from its fibrotic variant [ 88 , 89 ]. Some suggested that identifying a high level of serum IgG4 in one patient with Hashimoto’s thyroiditis represents an early predictor for developing its fibrotic variant [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…This immune attack targets the thyroid cells, causing damage and interfering with their normal function. Over time, this inflammation can lead to the development of Hashimoto’s thyroiditis ( 45 ). IgG4-related thyroid disease showed correlations with a younger age group, a higher occurrence in males, higher levels of thyroid autoantibodies, diffuse low echogenicity, and a higher prevalence of subclinical hypothyroidism ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The threshold to confirm increased IgG4-positive plasma cells ranges from more than 20 to more than 30 IgG4-positive plasma cells per high-power field by microscopic examination ( 78 81 ). The FNA specimens show lymphoplasmacytic infiltrates and oncocytes and the cytological features are usually classified as benign ( 80 ). Clinical history, radiological characteristics, and cytological features, such as abundant plasma cells, fibroblast, and epithelial atypia, should raise the suspicion of IgG4-related disease ( 82 ).…”
Section: Differentiating Benign From Malignant Thyroid Neoplasmsmentioning
confidence: 99%